De-risking primary prevention: role of imaging - Ahmed M. Shafter (SAGE Publishing, 2021)
Atherosclerotic cardiovascular disease (ASCVD) is a common disease among the general population, and includes four major areas: (1) coronary heart disease (CHD), manifested by stable angina, unstable angina, myocardial infarction (MI), heart failure, and coronary death; (2) cerebrovascular disease, manifested by transient ischemia attack and stroke; (3) peripheral vascular disease, manifested by claudication and critical limb ischemia; and (4) aortic atherosclerosis and aortic aneurysm (thoracic and abdominal). CHD remains the leading cause of death for both men and women in the United States. So, it is imperative to identify people at risk of CHD and provide appropriate medical treatment or intervention to prevent serious complications and outcomes including sudden cardiac death. Coronary artery calcification (CAC) is a marker of subclinical coronary artery disease. Therefore, coronary artery calcium score is an important screening method for Coronary artery disease (CAD). In this article, we performed a comprehensive review of current literatures and studies assessing the prognostic value of CAC for future cardiovascular disease (CVD) events. We searched PubMed, MEDLINE, Google Scholar, and Cochrane library. We also reviewed the 2018 American College of Cardiology (ACC)/American Heart Association (AHA) guideline on the assessment of CVD risk. A CAC score of zero corresponds to very low CVD event rates (∼1% per year) and hence a potent negative risk marker. This has been referred to as the ‘power of zero’ and affords the lowest risk of any method of risk calculation. It is now indicated in the 2018 ACC/AHA Cholesterol guidelines to be used to avoid statins for 5–10 years after a score of zero, and then re-assess the patient.